Pengaruh Minuman Kunyit Asam Terhadap Perubahan Skala Nyeri Haid pada Remaja di SMK Bhakti Asih Purwakarta - Maryamah, Neneng; Khaerunnisa, Gina (Jurnal Sosial Teknologi, 2025)
Based on data from the World Health Organization (WHO) in 2015, the incidence of dysmenorrhea is very high. It is estimated that 50% of women in the world experience dysmenorrhea, it was found that 1,815,211 people (90%) women experience dysmenorrhea with 11-15% experiencing severe dysmenorrhea. The incidence of dysmenorrhea in Indonesia is quite high, which is 54.89% of primary dysmenorrhea and 9.36% of secondary dysmenorrhea (Dahlan, 2017). Meanwhile, according to Andriyani (2016), the incidence of dysmenorrhea in West Java in 2015 was 72.89% primary dysmenorrhea and 27.11% of secondary dysmenorrhea and in Purwakarta as many as 63.2% of adolescents experienced dysminoria. Women who experience dysmenorrhea experience complaints such as pain or cramps, pain and are unable to work to take care of their own needs (Novia, 2013). Therefore, health workers must play an important role in helping health services, one of which is providing sour turmeric drinks to adolescents who experience menstrual pain. This study is to find out whether there is an effect of sour turmeric drink on reducing the intensity of menstrual pain in adolescents. This study is a quantitative research using a Quasy Experiment research design with a One Group Pretest- Posttest Design design using purposive sampling with a sample of 32 respondents, using the data obtained and then analyzed with the Wilxocon test using the help of the SPSS computer program. Study results: The results of the wilxocon analysis test had an effect on pain intensity in respondents before and after the experiment (giving sour kuyit drink) where the average value before being given was 6.28 ± 2.67 and after being given was reduced to 1.75 ± 1.918. P value 0.140 (p value > α) There was no effect of Menarce Age on Pain Scale in adolescents. The p value is 0.836 (p value > α) which means that there is no effect of menstrual length on the Pain Scale in Adolescents. There was a change in the pain scale before and after being given sour turmeric drink. Wilcoxon test results p value = 0.000 < ɑ (0.05) so that it can be concluded that there is a change in pain scale before and after being given sour turmeric drink, there is no relationship between menarche age and dysminorea pain scale with a p value of 0.140 > ɑ (0.05) nor is there a relationship between menarche age and dysminorea pain scale with a p value of 0.836 > ɑ (0.05). Continue to control primary dysmenorrhea factors that can be changed such as nutritional status and exercise habits through increasing knowledge and implementing a healthy lifestyle.